Abductor digiti minimi - Turski, Daniel (Canadian Medical Education Journal, 2018)
Medicine largely relies upon flexible, nimble, and agile thinking while working through complex differentials. Consequently, I like letting my mind roam while learning so as to enhance my mental flexibility. And this was one of the many images that popped into my mind while learning the musculoskeletal system. I’m also a visual learner.